Conceptualisation of Integration An Australian Muslim Counter-Narrative - Hersi, Abdi (Palgrave Politics of Identity and Citizenship Series, 2018)
'I have hardly come across a book that is as comprehensive and as insightful as this study, which clearly shows in how many different ways the notion of integration can be and has been conceptualised and interpreted, not only in the literature, but also in practice.' - Han Entzinger, Professor Emeritus of Migration and Integration Studies, Erasmus University Rotterdam, Netherlands This book identifies and examines the meanings of integration from the perspective of Australian Muslims, through analysis of focus group discussions and in-depth interviews in the South East Queensland region. It provides a comprehensive overview of Muslim conceptualisation of integration, and the author explores the various meanings Muslims ascribe to it, such as participation, belonging and contributing to the wider society By gaining an understanding of how Muslims define integration, this research can help policy makers, academics and settlement service providers to appreciate how culture and faith influence the meanings diverse groups give to certain accepted terms. It will be of interest to scholars and students in the fields of migration, mobility, integration and social cohesion.